Trans-Himalayan borderlands : livelihoods, territorialities, modernities - Smyer Yü, Dan; Michaud, Jean, 1957- (Asian borderlands., 2017)
The societies in the Himalayan borderlands have undergone wide-ranging transformations, as the territorial reconfiguration of modern nation-states since the mid-twentieth century and the presently increasing trans-Himalayan movements of people, goods and capital, reshape the livelihoods of communities, pulling them into global trends of modernisation and regional discourses of national belonging. This book explores the changes to native senses of place, the conception of border - simultaneously as limitations and opportunities - and what the authors call "affective boundaries," "livelihood reconstruction," and "trans-Himalayan modernities." It addresses changing social, political, and environmental conditions that acknowledge growing external connectivity even as it emphasises the importance of place